2016
DOI: 10.1186/s12920-016-0178-5
|View full text |Cite
|
Sign up to set email alerts
|

A unified analytic framework for prioritization of non-coding variants of uncertain significance in heritable breast and ovarian cancer

Abstract: BackgroundSequencing of both healthy and disease singletons yields many novel and low frequency variants of uncertain significance (VUS). Complete gene and genome sequencing by next generation sequencing (NGS) significantly increases the number of VUS detected. While prior studies have emphasized protein coding variants, non-coding sequence variants have also been proven to significantly contribute to high penetrance disorders, such as hereditary breast and ovarian cancer (HBOC). We present a strategy for anal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 186 publications
(186 reference statements)
0
14
0
Order By: Relevance
“…All rare variants were analyzed in silico using an IT-based method Mucaki et al, 2016) and a modified version of the Shannon pipeline utilizing TF information models built from ENCODE ChIP-seq datasets (Lu, Mucaki, & Rogan, 2017) to assess potential effects of variants on TF binding. Details of analyses are contained in Supporting Information Methods.…”
Section: In Silico Tf Binding Analysismentioning
confidence: 99%
“…All rare variants were analyzed in silico using an IT-based method Mucaki et al, 2016) and a modified version of the Shannon pipeline utilizing TF information models built from ENCODE ChIP-seq datasets (Lu, Mucaki, & Rogan, 2017) to assess potential effects of variants on TF binding. Details of analyses are contained in Supporting Information Methods.…”
Section: In Silico Tf Binding Analysismentioning
confidence: 99%
“…This facilitates prediction of phenotypic severity (Rogan and Schneider, 1995;von Kodolitsch et al, 1999;von Kodolitsch et al, 2006). The effects of splicing mutations can be predicted in silico by information theory (Rogan and Schneider, 1995;Kannabiran et al, 1998;Rogan et al, 1998;Svojanovsky et al, 2000;Rogan et al, 2003;Caminsky et al, 2014;Dorman et al, 2014;Viner et al, 2014;Caminsky et al, 2016;Mucaki et al, 2016;Shirley et al, 2019), and these predictions can be confirmed by in vitro experimental studies (Vockley et al, 2000;Lamba et al, 2003;Rogan et al, 2003;Khan et al, 2004;Susani et al, 2004;Hobson et al, 2006;Caux-Moncoutier et al, 2009;Olsen et al, 2014;Vemula et al, 2014;Peterlongo et al, 2015). Strengths of one or more splice sites may be altered and, in some instances, concomitant with amino acid changes in coding sequences (Rogan et al, 1998;Peterlongo et al, 2015).…”
Section: Introductionmentioning
confidence: 98%
“…As an alternative for non-coding variants, bioinformatics in silico analysis are useful to prioritize the variants that are located in DNase I, FAIRE peaks of open chromatin and TF consensus binding sites. Additionally, Information theory analysis has been used to evaluate if the binding strength of several TFs are predicted to be altered by BRCA1/2 variants [ 75 ]. Moreover, the potential effect of a single nucleotide variant on RNA secondary structure can be tested by the prediction software SNPfold [ 76 ] and confirmed by the detection of covalent adducts in mRNA by the SHAPE assay [ 77 ].…”
Section: Methods To Assess the Pathogenicity Of Brca1/2 mentioning
confidence: 99%